Acanthomatous Ameloblastoma: A Rare Entity - Kiran Vallamchetla; Sandhya Chitty; Kotya Naik Maloth; Sridevi Ugrappa (Wolters Kluwer Medknow Publications, 2018)
Ameloblastoma is a slow-growing and locally aggressive true neoplasm of enamel organ-type tissue which does not undergo differentiation to the point of enamel formation. It is most commonly seen in the posterior region of mandible, less commonly in anterior region, and rarely crossing the midline. It occurs in age ranging from 20 to 50 years with equal frequencies between sexes. It has a high recurrence rate due to its capacity to infiltrate marrow spaces with pseudopods without concomitant resorption of trabecular bone. As a result, the margins of the tumor are not clearly evident radiographically or grossly during operation, and the lesion frequently recurs after inadequate surgical removal. Here, we report a rare case of acanthomatous ameloblastoma present in a young male in the anterior mandibular region crossing the midline, along with an added emphasis on its review.